Planning and managing public relations campaigns : a strategic approach - Gregory, Anne, 1953- (PR in practice, 2015)
"Getting a public relations campaign or program off the ground can seem an overwhelming task. But, as with any project, the secret of success lies in good planning and effective management. This fully updated fourth edition of Planning and Managing Public Relations Campaigns provides a revised and more dynamic 12-step planning model to help all practitioners implement and run a campaign. With new coverage of key social media developments and using new case studies, Anne Gregory covers vital topics including: the role of PR in organizations; the importance of context; research and analysis; communication theory; setting objectives; publics and content; strategy and tactics; timescales and resources; evaluation and review. "--